Martyrdom, Memory, and Identity: A Qualitative Discourse Analysis of Operation Bunyan-um-Marsoos in Pakistan’s Strategic Culture: https://doi.org/10.5281/zenodo.16936139 - Junaid Ali Jalbani (`, 2025)
This paper discusses the events of Operation Bunyan-um-Marsoos, a military action taken by Pakistan in response to the 2025 Pahalgam attack, in the contexts of strategic retaliation and symbolic identity formation. Placed in the historical framework of Indo-Pakistani conflict, the operation can be viewed not only as a step of calculated deterrence but also as a performative story that is based on Islamic symbolism and collective memory. With the references to the Quran especially Surah Al-Saff (61:4), the operation was presented as a divine obligation, which strengthened national solidarity and national endurance. By analysing qualitative discourse of state rhetoric, media coverage, and commemorations like Youm-e-Tashakur the study exposes the instrumentalization of martyrdom narratives and memory politics to establish the military action as a long-lasting cultural and ideological script. The results show how realist logic of security and constructivist identity making are intertwined in Pakistan, which in part explains how the country uses religious symbolism to justify its actions both at home and abroad. The study can inform the wider perspectives of hybrid warfare and identity politics and the importance of collective memory in the conflict patterns in South Asia, as well as pointing to the dangers of the further development of identity-based antagonisms in the region. Keywords: Operation Bunyan-Um-Marsoos, Martyrdom, Collective Memory, Identity Construction, Indo-Pakistan Relations, Symbolic Warfare, Islamic Symbolism